Cryoresistance Differences Between Species of Autotrops From Polar Regions Sensed by Chlorophyll Fluorescence - Puhovkin, Anton; Hájek, Josef; Giordano, Davide; Sekerák, Jiři; Bartak, Miloš (Problems of Cryobiology and Cryomedicine, 2023)
Lichens from the cold regions of Earth exhibit high, but different degree of tolerance to drought and freeze stresses. Therefore, three lichen species Xanthoria elegans, Umbilicaria cylindrica, Usnea sphacelata, and a representative of extremophilic cyanobacteria Nostoc commune were selected to measure temperature response curves of chlorophyll fluorescence parameters in cooling experiment using a constant rate of cooling from 20 to –45°C. Two chlorophyll fluorescence parameters (FV/FM – potential yield of photosynthetic processes in photosystem II and ΦPSII – effective quantum yield) were measured with a modulated fluorometer. For all experimental species, the temperature-response curves of II FV/FM and ΦPSII showed typical triphasic shape: plateau (temperature decrease from 20 to –5°C), decline, and a shoulder reaching the critical point. The phase typically formed a S-curve of different shape as dependent on species and chlorophyll fluorescence parameter. U. cylindrica was the most cryoresistant in terms of photosynthetic processes ongoing in thylakoid membrane of chloroplast at below zero temperature. Probl Cryobiol Cryomed 2023; 33(1):025–037